Perubahan Musiman (Seasonality) Pasar Modal dan Efek Kontagion di Negara-negara ASEAN - Dwipraptono Agus Harjito (Jurnal Siasat Bisnis, 2010)
This study was to investigate the contagion effect of seasonality in stock markets in the ASEAN region. The study employed the month-end closing prices of each country’s based stock market indexes over the period of January 1990 to December 2007. Using Granger causality test, the study found evidence of causal linkages in the markets with Singapore as the leader in majority of the cases. The study also investigated for causal linkages due specifically to seasonality effect. The results deviated from those of the general market performance with respect to the leader-follower linkages but its lended strong support to the view that seasonality effect in some stock markets are contagious. Keywords: seasonality effect; contagion effect; ASEAN countries